Evaluasi Kuat Tekan Beton Menggunakan Pengujian Non Destructive (Hammer Test) Studi Kasus: Proyek Pembangunan Tambatan Perahu, Desa Uludala, Kab. Ende - Frianggi Sofia D Mansari; Reyneldis L Fernandez; Wenceslaus R Fernandez (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The construction of a boat mooring/people’s pier in Ende Regency is one of the government's efforts to assist the community in obtaining services for transportation access. The construction of a boat mooring/people’s pier at Ropa Beach, Uludala Village, Maurole District aims to provide a supporting facility for the community to moor boats, accelerate economic progress and serve the social needs of the community. This study evaluated the quality of installed concrete on a 25 cm × 25 cm mini pile structure in the construction of a community boat mooring/pier using the non-destructive Hammer Test method. The test results showed a strong relationship between the rebound number and the compressive strength of the concrete, with a regression equation of Ŷ = 1.9531x – 39.265, a determination coefficient of 0.9991 or 99.91%. and a correlation coefficient of 0.99955. The average concrete compressive strength value reached 59.660 MPa or equivalent to the quality of concrete (K-608.53), exceeding the minimum specifications of K-450. These results indicate that the quality of the installed concrete has met or even exceeded the planning standards.